Qualitative Fingerprint Analysis and Multidirectional Assessment of Different Crude Extracts and Essential Oil from Wild Artemisia santonicum L. - ŞENKARDEŞ, İSMAİL (MDPI, 2019)
Artemisia species are used as folk medicines in several countries. This work was aimed to shed more light on the effect of methanol, water, ethyl acetate extracts, and essential oil (EO) of A. santonicum on selected enzymes (cholinesterase, tyrosinase alpha-amylase, and alpha-glucosidase) as well of their antioxidant and pharmacological effects. The chemical profile of the essential oil was determined using gas chromatography coupled to mass spectrometry (GC-MS) analysis, while the extracts were chemically characterized by high performance liquid chromatography coupled to mass spectrometry (HPLC-MS). Forty-nine constituents were identified and camphor (36.6%), 1,8-cineole (10.2%), alpha-thujone (10.1%), borneol (4.5%), and beta-thujone (3.6%) were the major components. Overall, 45, 74, and 67 components were identified from the ethyl acetate, methanol, and water extracts, respectively. The EO and extracts showed significant antioxidant properties, in a cell-free model; particularly, methanol and water extracts revealed promising sources of antioxidant compounds. Additionally, we evaluated protective effects of EO and extracts in isolated rat colon tissue challenged with lipopolysaccharide (LPS), as an ex vivo model of colon inflammation, and human colon cancer HCT116 cell line. Particularly, we observed that, among all tested samples, A. santonicum ethyl acetate displayed the best pharmacological profile, being able to blunt LPS-induced levels of all tested biomarkers of inflammation and oxidative stress, including colon nitrites, lactate dehydrogenase, prostaglandin E-2, and serotonin. Additionally, this extract was also able to reduce HCT116 cell viability, thus suggesting potential antiproliferative effects against colon cancer cells. Based on our results, A. santonicum has great potential for developing novel functional agents including pharmaceuticals, cosmeceuticals, and nutraceuticals.
Keywords: Artemisia; essential oil; bioactive compounds; antioxidant; enzyme inhibition; INFLAMMATORY-BOWEL-DISEASE; CHEMICAL-COMPOSITION; ANTIOXIDANT ACTIVITY; ANTIMICROBIAL ACTIVITY; INHIBITION ACTIVITIES; EXPERIMENTAL COLITIS; ALPHA-AMYLASE; AERIAL PARTS; SEROTONIN; FLAVONOIDS